Intertwined worlds : medieval Islam and Bible criticism - Lazarus-Yafeh, Hava (Princeton, New Jersey : Princeton University Press, 1992)
Exploring the lively polemics among Jews, Christians, and Muslims during the Middle Ages, Hava Lazarus-Yafeh analyzes Muslim critical attitudes toward the Bible, some of which share common features with both pre-Islamic and early modern European Bible criticism. Unlike Jews and Christians, Muslims did not accept the text of the Bible as divine word, believing that it had been tampered with or falsified. This belief, she maintains, led to a critical approach to the Bible, which scrutinized its text as well as its ways of transmission. In their approach Muslim authors drew on pre-Islamic pagan, Gnostic, and other sectarian writings as well as on Rabbinic and Christian sources. Elements of this criticism may have later influenced Western thinkers and helped shape early modern Bible scholarship. Nevertheless, Muslims also took the Bible to predict the coming of Muhammad and the rise of Islam. They seem to have used mainly oral Arabic translations of the Hebrew Bible and recorded some lost Jewish interpretations. In tracing the connections between pagan, Islamic, and modern Bible criticism, Lazarus-Yafeh demonstrates the importance of Muslim mediation between the ancient world and Europe in a hitherto unknown field. Originally published in 1992. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- Contents -- Abbreviations -- Preface -- CHAPTER ONE. Introduction -- CHAPTER TWO. Muslim Arguments against the Bible -- CHAPTER THREE. Ezra-'Uzayr: The Metamorphosis of a Polemical Motif -- CHAPTER FOUR. Muslim Bible Exegesis: The Prediction of Muhammad and Islam -- CHAPTER FIVE. Muslim Authors and the Problematics of Arabic Translations of the Bible -- CHAPTER SIX. Conclusion: From Late Antiquity to the Beginnings of Modern Bible Criticism -- Appendix: Jewish Knowledge of, and Attitudes toward, the Qur'an -- List of Biblical Verses Cited -- List of Qur'anic Verses Cited -- Index.
Includes bibliographical references and index.
Print version record.
In English.
Master record variable field(s) change: 630, 650
Keywords: Bible. -- Islamic interpretations; Bible. -- Criticism, interpretation, etc. -- History -- Middle Ages, 600-1500.; Bible; Islam -- Relations -- Judaism; Judaism -- Relations -- Islam; Islam -- Relations -- Christianity; Christianity and other religions -- Islam; RELIGION -- Islam -- General; RELIGION -- Biblical Studies -- Old Testament; RELIGION -- Judaism -- Sacred Writings; Christianity; Interfaith relations; Islam; Islamic interpretations of sacred works; Judaism; 600-1500; Electronic books; Criticism, interpretation, etc; History